PROTOTYPE PERANCANGAN ALAT PENDETEKSI KETINGGIAN TANDON AIR DI RSUD DR. GUNAWAN MANGUNKUSUMO BERBASIS ARDUINO UNO - Daniel Rudjiono; Dani Sasmoko; Hendra Cahya Ardhy Syahputra (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Water is an essential need for human life, especially in hospitals which require a constant supply of clean water. Dr. Gunawan Mangunkusumo Regional Public Hospital, Semarang Regency, is facing problems in managing the water reservoir due to a lack of monitoring and an automatic filling system. This leads to water wastage and inconvenience. This article discusses the design of a water level detection device prototype based on the Wemos D1 Mini microcontroller to overcome this problem.3 The system utilizes the HC-SR04 ultrasonic sensor to measure water level and display the information on an LCD and web server. The microcontroller controls the water pump automatically based on the detected water level, which is categorized into three levels: LOW, MEDIUM, and HIGH. Test results show that the system can measure water levels accurately and control the water pump effectively.This prototype is expected to assist Dr. Gunawan Mangunkusumo Regional Public Hospital in improving water management efficiency, ensuring a sustainable supply of clean water, and reducing the workload of staff